Economic analysis of solar photovoltaic power plant planning at Taman Melati Depok Apartment - Dhona, Roma; Dalimi, Rinaldy (Universitas Negeri Padang, 2023)
Currently, Indonesia is still using fossil fuel power plants. The high use of fossil fuels will harm the environment, therefore to reduce the use of fossil fuels, it is necessary to develop renewable energy power plants, one of which is a solar photovoltaic power plant. This study discusses the economic analysis of planning a soalr photovoltaic power plant at the Taman Melati Depok Apartment which is connected to the PLN network with the PVsyst software. This PLTS plan will be built on the roof of the apartment using an area of 437 m2 with generated power of 90,400 Wp. Using solar modules with a capacity of 565 Wp as many as 160 modules. This PLTS can generate electricity per year 116600 kWh/year. The Cost of Energy (COE) for this PLTS is Rp.735.39/kWh. Economic analysis uses Net Present Value (NPV), Profitability Index (PI), and Discounted Payback Period (DPP) to determine whether this PLTS is feasible or not. Based on the calculation result, the NPV value is Rp. 608,793,939.29, while the PI value is 1.587 and the DPP value is around 12 years and 9 months, which is faster than the project age, which is 30 years. Thus the investment in the Taman Melati Apartment PLTS project is feasible to continue.